Recuperação de áreas em incompatibilidade legal de uso da terra: o caso da bacia hidrográfica do arroio Manoel Alves, Itaara, RS - Schneider, Cristina (2010)
This research was developed with the purpose of analyzing areas of land use legal incompatibility in watershed from Manoel Alves Stream, aiming to increase water production, according to what is prescribed in Municipal Director Plan, which among others determinations, seeks the implantation of public politics for sustainability. To reach this purpose, firstly, it was elaborated the land use map through images from LANDSAT 5 satellite, 3, 4 and 5 bands, of October 20th, 2009, where were identified five categories: water; mining area; building area; cultures; vegetation. After, from the established in Environmental Law, it was elaborated the map of permanent preservation areas, from the images of LANDSAT 5 satellite and from the topographies of Camobi NW and SW and Santa Maria NE and SE, of scale 1:25.000. In the identification of areas of land use legal incompatibility, it was carried out a combination between information plans map of used land and the permanent preservation areas, where it was ascertained that 28,82% from the total of permanent preservation areas of the watershed has being occupied by dwellings, by cultures and by mining exploitation. Through the analyses of the map of land use legal incompatibility, it was perceived that part of them is located in rural areas. Therefore, it was pointed out policies for recuperation of areas in incompatibility of use, based on what ANA establishes, that considers the farmer as a water producer. In Water Producer Program, the watershed is seen as water producer, and the ones that maintain it are the producers, for depends on the use that be made in the surroundings of the springs, it can collaborate to the availability of water resources with quality or without. In order to improve the water production, ANA proposes the adoption of preservation practices supported by three pillars: riparian vegetation conservation and recuperation, soil conservation practices and implementation of environmental sanitation in the property. This research is justified by the need pointed in Municipal Director Plan that deals with Environmental Municipal Politics, and that, among other points, predicts the organization of Special Areas of Environmental Interest (AEIA) and incentives the organization of Private Reserves of Natural Heritage (RPNN), besides the elaboration of a Municipal Environmental Plan. This Plan will embrace the protected areas mapping, according to the law, and incentive ways offered by the local authority for environmental preserve and recuperation actions.